Mesopelagic Prokaryotes Alter Surface Phytoplankton Production during Simulated Deep Mixing Experiments in Eastern Mediterranean Sea Waters - Hazan, Or; Silverman, Jacob; Sisma-Ventura, Guy; Ozer, Tal; Gertman, Isacc; Shoham-Frider, Efrat; Kress, Nurit; Rahav, Eyal (Frontiers in Marine Science, 2018)
Mesopelagic prokaryotes (archaea and bacteria), which are transported together with nutrient-rich intermediate-water to the surface layer by deep convection in the oceans (e.g., winter mixing, upwelling systems), can interact with surface microbial populations. This interaction can potentially affect production rates and biomass of surface microbial populations, and thus play an important role in the marine carbon cycle and oceanic carbon sequestration. The Eastern Mediterranean Sea (EMS) is one of the most oligotrophic and warm systems in the world’s oceans, with usually very shallow winter mixing (<200 m) and lack of large-size spring algal blooms. In this study, we collected seawater (0-1500 m) in 9 different cruises at the open EMS during both the stratified and the mixed seasons. We show that the EMS is a highly oligotrophic regime, resulting in low autotrophic biomass and primary productivity and relatively high heterotrophic prokaryotic biomass and production. Further, we simulated deep water mixing in on-board microcosms using Levantine surface (LSW, 0.5 m) and intermediate (LIW, 400 m) waters at a 9:1 ratio, respectively and examined the responses of the microbial populations to such a scenario. We hypothesized that the LIW, being nutrient-rich (e.g., N, P) and a ‘hot-spot’ for microbial activity (due to the warm conditions that prevail in these depths), may supply the LSW with not only key-limiting nutrients but also with viable and active heterotrophic prokaryotes that can interact with the ambient surface microbial population. Indeed, we show that LIW heterotrophic prokaryotes negatively affected the surface phytoplankton populations, resulting in lower chlorophyll-a levels and primary production rates. This may be due to out-competition of phytoplankton by LIW populations for resources and/or by a phytoplankton cell lysis via viral infection. Our results suggest that phytoplankton in the EMS may not likely form blooms, even after exceptionally deep winter mixing, and therefore have a very small overall effect on the vertical flux of organic matter to the deep sea.